The impact of personal finance on well-being: Evidence from Vietnamese university students - Huong, Dao Lan; Huong, Vu Thi (Edelweiss Applied Science and Technology, 2025)
This research investigates the impact of personal financial anxiety on subjective well-being among Vietnamese university students within the context of the post-pandemic environment. A cross-sectional survey was administered to a sample of 663 students at the Vietnam Women’s Academy. Data collection involved the use of validated measurement scales assessing dimensions such as life satisfaction, mental well-being, and interdependent happiness. The analytical approach employed multiple linear regression analyses to evaluate the predictive influence of financial anxiety on various aspects of well-being. The results indicated that financial anxiety significantly negatively affected life satisfaction (β = –0.123, p = .002) and perceived overall happiness (β = –0.104, p = .007). However, no statistically significant relationships were observed between financial anxiety and mental well-being or interdependent happiness. These findings suggest that financial anxiety constitutes a psychological risk factor that diminishes positive life evaluations, independent of actual income levels or social support systems. The study underscores the importance of developing comprehensive student support initiatives that integrate financial literacy education, emotional regulation training, and accessible mental health services. Such programs are essential to enhance resilience and foster sustainable well-being amid ongoing economic challenges.